Toward a Post-Sraffian Theory of Income Distribution - Roncaglia, A. (Journal of Income Distribution®, 1994)
After recalling the Sraffian critiques to marginalist distribution theory, and hence the need for a different approach, the paper illustrates the classical conceptualization of social classes and its flexibility for the application to the modern world. The relationships among market forms-above all oligopoly, mark-up pricing, and income distribution-are then discussed, in search of a theoretical framework for the analysis of the evolution of distributive variables over time: an approach suggested as superior to the traditional one which aims at determining equilibrium values for the distributive variables at a moment in time.